Yb(OTf)3 Catalyzed Synthesis, Antimicrobial and Insecticidal activity of some Biscoumarins - Tekalea, Sunil U.; Thorea, Shivaji N.; Dodkeyb, Alaknanda M.; Kendrekarc, Pravin S.; Pawar, Rajendra P. (Chemistry & Biology Interface, 2018)
In the present study, we report Yb(OTf)3 catalyzed synthesis of biscoumarins by pseudo three-component reaction of aldehyde and 4-hydroxycoumarin. The synthesized biscoumarins were evaluated for antimicrobial and insecticidal activity. Results of antimicrobial activity were found to be moderate to good in terms of zones of inhibition and MIC values against E. coli, P. vulgaris and S. aureus. The compounds were inactive against the used fungal strains except B4 in case of Penicillium. Insecticidal activity of the biscoumarins B-1, B-3, B-5 and B-11 was found to be good exhibiting 70-75% mortality effect on Callosobruchus maculatus.
Published Article
Keywords: Yb(OTf)3; Biscoumarins; Antimicrobial; Insecticidal